PENGGUNAAN VIDEO INTERAKTIF BERBASIS CAI TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK AUTIS DI SEKOLAH DASAR - RAHAYU, SRI; , BUDIYANTO (Jurnal Pendidikan Khusus, 2019)
AbstractThis research is motivated by the problems of autistic students without intellectual barriers that experience difficulties in beginning reading, including pronounciation of words, awareness of sounds, and identification of words beginning with vowels and consonants and words containing sounds ng. The media used in early reading learning in the form of conventional media such as printed books and blackboards. Based on these problems, this study aims to examine the effect of using CAI-based interactive videos on the ability to read the beginning, on aspects of recognizing letters, reading syllables, reading words, and reading simple sentences. Autistic students are taught interactively and provide stimuli to students to carry out reading activities. The quantitative approach, with the type of pre-experimental research method and the research design in the form of one group pre test post test design, was applied to the research subjects totaling 6 low-grade autistic students with a low level of initial reading ability and need to be improved. Data collection techniques are oral test pre test and post test, and data analysis using non-parametric statistics with the Wilcoxon match pairs test test formula. The results showed an increase in the ability to read the beginning of autistic students before and after the implementation of CAI-based interactive videos, which is indicated by the pre-test value with an average yield of 46.7 and post test scores with an average yield of 66.6. In addition, the results of the study also show that the T value of 0 is equal to the value of T table with a critical value of 5% of 0. If the value of T = T table is 0, it indicates that the working hypothesis (Ha) is accepted and the null hypothesis (rejected), and interpreted that there is an effect of using CAI-based interactive videos on the ability to read the beginning of autistic students at Ketintang II Surabaya elementary school. Keyword : Interactive Video, Read the Beginning, AutismAbstrakPenelitian ini dilatarbelakangi oleh permasalahan peserta didik autis tanpa hambatan intelektual yang mengalam kesulitan dalam membaca permulaan, meliputi pelafalan kata, kesadaran bunyi , dan identifikasi kata yang diawali huruf vokal dan konsonan serta kata yang mengandung bunyi ng. Media yang digunakan dalam pembelajaran membaca permulaan berupa media konvensional seperti buku cetak dan papan tulis. Berdasar pada permasalahan tersebut, penelitian ini bertujuan untuk menguji pengaruh penggunaan video interaktif berbasis CAI terhadap kemampuan membaca permulaan, pada aspek mengenal huruf, membaca suku kata, membaca kata, dan membaca kalimat sederhana. Peserta didik autis diajarkan secara interaktif dan memberikan stimulus kepada peserta didik untuk melakukan kegiatan membaca. Pendekatan kuantitatif, dengan jenis metode penelitian pre eskperimental dan rancangan penelitian berupa one group pre test post test design diterapkan pada subjek penelitian berjumlah 6 peserta didik autis kelas rendah dengan tingkat kemampuan membaca permulaan yang masih rendah serta perlu ditingkatkan. Teknik pengumpulan data yaitu tes lisan pre test dan post test, serta analisis data menggunakan statistik non parametric dengan rumus uji wilcoxon match pairs test. Hasil penelitian menunjukkan peningkatan kemampuan membaca permulaan peserta didik autis sebelum dan sesudah diterapkannya video interaktif berbasis CAI, yang ditunjukkan oleh nilai pre test dengan hasil rata ? rata sebesar 46,7 dan nilai post test dengan hasil rata ? rata sebesar 66,6. Selain itu, hasil penelitian juga menunjukkan nilai T sebesar 0 sama dengan nilai T tabel dengan nilai kritis 5% sebesar 0. Jika nilai T = T tabel yaitu 0, maka menunjukkan bahwa hipotesis kerja (Ha) diterima dan hipotesis nol (ditolak), dan diinterpretasikan bahwa terdapat pengaruh penggunaan video interaktif berbasis CAI terhadap kemampuan membaca permulaan peserta didik autis di SDN Ketintang II Surabaya. Kata kunci : Video Interaktif, Membaca Permulaan, Autis